Analisis Penanganan Anak Berhadapan dengan Hukum dalam Kasus Cyberbullying di Kota Baubau - Hasirudin Hasri; Hayun Hayun; Al Hiday Nur; Revalina Nur aliyah Priadi; L.M. Jumardin Nur Akbar (Journal Law and Government, 2026)
Cyberbullying has evolved into a form of digital violence that increases the risk of children being involved in the Juvenile Criminal Justice System (SPPA), while diversion mechanisms are still oriented towards resolving cases after the crime has occurred. This study aims to analyze the characteristics of handling cyberbullying against children in Baubau City and formulate a model for strengthening diversion that is responsive to the escalation of digital conflict. The study uses a socio-legal approach, combining normative analysis of laws and regulations with empirical research through semi-structured interviews. The results show that handling cyberbullying is still dominated by a preventive approach through outreach, cyber patrols, and digital literacy, while diversion is only implemented after the child enters the criminal justice process according to the SPPA provisions. These findings indicate a gap between the characteristics of digital conflict escalation and the current design of child protection. This research offers a Preventive Diversion Model Based on Digital Conflict Escalation, which repositions diversion as an early intervention mechanism through the integration of the roles of schools, DP3A, and the police to prevent children from entering the criminal justice system and strengthen child protection policies that are adaptive to the development of cybercrime.